2017
DOI: 10.1002/ccd.27412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anemia on long‐term outcomes after percutaneous coronary intervention for chronic total occlusion

Abstract: Although anemia is associated with an increased all-cause mortality in patients undergoing CTO PCI, the survival benefit associated with successful CTO recanalization is maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
(80 reference statements)
3
6
0
Order By: Relevance
“…Preprocedural anemia has been associated with a higher incidence of adverse follow‐up outcomes in patients undergoing elective PCI or PCI for ACS 1–7 . However, the effect of anemia on follow‐up outcomes after CTO PCI has only been evaluated in one study 8 that showed higher follow‐up MACE (hazard ratio [HR]: 1.26; 95% CI: 1.02–1.55; p = 0.03) and all‐cause mortality (HR: 2.26; 95% CI: 1.71–2.98; p < 0.001) in anemic patients, similar to our study (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preprocedural anemia has been associated with a higher incidence of adverse follow‐up outcomes in patients undergoing elective PCI or PCI for ACS 1–7 . However, the effect of anemia on follow‐up outcomes after CTO PCI has only been evaluated in one study 8 that showed higher follow‐up MACE (hazard ratio [HR]: 1.26; 95% CI: 1.02–1.55; p = 0.03) and all‐cause mortality (HR: 2.26; 95% CI: 1.71–2.98; p < 0.001) in anemic patients, similar to our study (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Approximately 15%-17% of patients undergoing CTO PCI are anemic. 6,8 In a previous singlecenter study on 1964 patients undergoing CTO PCI, anemic patients had higher adjusted mortality during follow-up. 8 However, these findings have not been replicated in larger, multicenter cohorts.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several important prognostic factors, such as reduced left ventricular ejection fraction [11], anemia [12], and hemodialysis [13], have been identified, albeit the prognostic benefit of successful CTO-PCI does not differ according to the presence or absence of these prognostic factors. These factors are helpful in identifying high-risk patients who require close clinical follow-up and/or aggressive risk factor modification.…”
Section: Introductionmentioning
confidence: 99%